2010
DOI: 10.1007/s10765-010-0783-z
|View full text |Cite
|
Sign up to set email alerts
|

Realization of Fe–C Eutectic Point Using an Alumina Crucible

Abstract: As another crucible material for metal-carbon eutectic points, alumina ceramic was used in the first trial to make an Fe-C eutectic point for the calibration of a thermocouple. Its melting and freezing behavior was tested 26 times with a type S thermocouple at various melting offset temperatures, namely, +4 • C, +9 • C, and +19 • C, and at a fixed freezing offset temperature of −11 • C. The melting emf is reproducible independent of the melting offset temperatures, and the standard deviation of the 26 melting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…If the weak mechanical resistance of alumina at high temperature is overcome, the Si-SiC eutectic point in an alumina crucible can be useful in thermometry, especially for the calibration of thermocouples. Present studies on making metal-carbon cells using an alumina crucible are going on at our laboratory [15]. Based on this result, we made a Si-SiC cell for thermocouple thermometry and evaluated its melting and freezing behaviour using a Pt/Pd thermocouple.…”
Section: Resultsmentioning
confidence: 99%
“…If the weak mechanical resistance of alumina at high temperature is overcome, the Si-SiC eutectic point in an alumina crucible can be useful in thermometry, especially for the calibration of thermocouples. Present studies on making metal-carbon cells using an alumina crucible are going on at our laboratory [15]. Based on this result, we made a Si-SiC cell for thermocouple thermometry and evaluated its melting and freezing behaviour using a Pt/Pd thermocouple.…”
Section: Resultsmentioning
confidence: 99%
“…The Fe-C eutectic fixed-point temperature [7,8] is expected to be 1153 • C, which is close to the copper point but nevertheless provides a convenient supplementary calibration point. In particular, Fe-C eutectic fixed-point cells are important for the nuclear industry since they are expected to be significantly more stable under irradiating/ionizing conditions than either copper or Co-C because the small neutron capture cross-section of iron results in a low transmutation rate [9].…”
Section: Introductionmentioning
confidence: 98%
“…The small difference in cell volume between the cells was due to the machining tolerance variation of the ceramic materials. An electric high-temperature furnace with six vertical U-shaped Kanthal super heaters was used [4,9,12,13]. To protect the Fe sample from oxidation at high temperature, a mixture of Ar (99.999% purity) and 0.5 vol% hydrogen continuously flowed into the cell during all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, alumina ceramic was selected as a possible solution. It has been reported that Fe-C [9], Ni [10], Ni-Ag [11] and Pd [12] cells were successfully fabricated using alumina crucibles without breakage after successive melting and freezing cycles. Thus, Fe cells were made using alumina crucibles.…”
Section: Introductionmentioning
confidence: 99%